1996
DOI: 10.1080/135468096396668
|View full text |Cite
|
Sign up to set email alerts
|

Delusions Demand Attention

Abstract: We used a variant of the Stroop paradigm to investigate attention bias in a young woman (JK) with delusional beliefs that she had died and that members of her family had changed. JK was shown sets of words printed in different colours of ink, and was asked to name the colour of each word. Sets of words were chosen which related to her delusions, and to possible contributory moods. The times taken by JK to colour-name words in these lists were compared with her times to colour-name sets of neutral words. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 16 publications
2
20
1
1
Order By: Relevance
“…Rossell, Shapleske, and David (1998) recently used a sentence verification task to investigate semantic memory in patients with delusions. They established that cognitive bias towards certain emotional themes may underlie illogical semantic connections and delusions, in agreement with previous studies on attentional bias towards delusion-sensitive material (Bentall, Kaney, & Bowen-Jones, 1995;Leafhead et al, 1996). However, the study also indicated that higher order semantic processes may be disturbed in patients with delusions.…”
Section: Delusionssupporting
confidence: 84%
“…Rossell, Shapleske, and David (1998) recently used a sentence verification task to investigate semantic memory in patients with delusions. They established that cognitive bias towards certain emotional themes may underlie illogical semantic connections and delusions, in agreement with previous studies on attentional bias towards delusion-sensitive material (Bentall, Kaney, & Bowen-Jones, 1995;Leafhead et al, 1996). However, the study also indicated that higher order semantic processes may be disturbed in patients with delusions.…”
Section: Delusionssupporting
confidence: 84%
“…The emotional Stroop task (Stroop, 1935) measures attentional biases to emotionally relevant stimuli and has been widely used in psychosis research (Bentall and Kaney, 1989;Bentall et al, 1995;Leafhead et al, 1996). Participants indicate the colors of either emotionally valenced or neutral words as quickly as they can.…”
Section: Stroop Taskmentioning
confidence: 99%
“…Individuals diagnosed with psychotic disorders have been found to selectively attend to threat words (Bentall and Kaney, 1989;Fear and Healy, 1996;Kinderman et al, 2003) and threatening visual pictures (Phillips et al, 2000) and to demonstrate a recall bias to threat words (Bentall et al, 1995) significantly more than do individuals with no diagnosis of a psychotic disorder. The degree of attentional bias to threat has been shown to be positively associated with the severity of positive psychotic symptoms (Fear and Healy, 1996), and the specificity of attentional biases is also linked with the content of delusional beliefs (Leafhead et al, 1996).…”
mentioning
confidence: 99%
“…Emotion-related WM deficits and PFC dysfunction are seen both in schizophrenia and bipolar disorder with psychosis and are consistently linked with positive symptoms in these disorders (Bentall & Kaney, 1989; Besnier et al, 2011; Epstein et al, 1999; Fear et al, 1996; Leafhead et al, 1996; Mohanty et al, 2008). Thus, in the present study we hypothesized that increased DLPFC and VLPFC activity due to emotion-related WM disruption will be associated with psychotic symptom dimension even when controlling for groups based on Diagnostic and Statistical Manual of Mental Disorders IV (DSM-IV)(American Psychiatric Association, 1994) categories.…”
Section: Transdiagnostic Hypothesismentioning
confidence: 99%